The Political Thought of Mao Tse Tung - Stuart R. Schram (Preager Publisher, 1971)
This book still constitutes only a provisional and inadequate account of a very complex subject. The information which has become available in the course of the cultural revolution calls into question much that we have thought in the past, both about Mao Tse-tung's career and about his ideas and strategy.